2012
DOI: 10.1186/1477-7819-10-121
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid involvement in thyroid cancer: an unforeseen event

Abstract: BackgroundParathyroid metastatic disease from thyroid cancer has not been studied extensively, mainly due to the need for parathyroid preservation during thyroid surgery.MethodsWe reviewed files from 1,770 patients with thyroid cancer followed up in our department and 10 patients with parathyroid metastases (0.5%) were identified. Patient and tumor characteristics were recorded.ResultsSix out of ten patients had metastases from papillary thyroid cancer, three from follicular thyroid cancer and one from anaplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…The infiltrative or metastatic PTG involvement is a rare entity in patients with DTC. In our cohort, the frequency of PTG was 1.94%, which is consistent with other reported results [1][2][3]. However, the frequency was much higher among patients with histologically proven advertent or inadvertent Parathyroidectomy (8.38%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The infiltrative or metastatic PTG involvement is a rare entity in patients with DTC. In our cohort, the frequency of PTG was 1.94%, which is consistent with other reported results [1][2][3]. However, the frequency was much higher among patients with histologically proven advertent or inadvertent Parathyroidectomy (8.38%).…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of parathyroid glands (PTG) involvement in differentiated thyroid carcinoma (DTC) and its prognosis are not well known, since the invasion of the PTG is not routinely sought during surgery [1]. Reported incidence rate of PTG involvement in PTC is 0.5%-7.9% depending on number of retrieved PTG postthyroidectomy histopathological examination [2]. However the true prevalence of PTG infiltration is difficult to estimate during the thyroidectomy as special attention is paid to the preserve the PTG [3].…”
Section: Introductionmentioning
confidence: 99%
“…Metastases to the parathyroids are rare and are nearly always identified as part of extensive metastatic disease, with only 3.2% of cases reported as isolated metastases (Chrisoulidou et al 2012, Lee et al 2013, Shifrin et al 2015, Bauer et al 2018. Autopsy studies have suggested that the prevalence of the incidental involvement of the parathyroids by metastatic tumours varies between 5.3 and 19%, with breast carcinoma being the most common tumour (Bauer et al 2018) (Table 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…Autopsy studies have suggested that the prevalence of the incidental involvement of the parathyroids by metastatic tumours varies between 5.3 and 19%, with breast carcinoma being the most common tumour (Bauer et al 2018) (Table 1). A recent review (Bauer et al 2018) identified that 66.9% of parathyroid metastases originated from breast carcinoma, followed by melanoma (11.8%) and lung carcinoma (5.5%); approximately 5.5% were 'tumour-to-tumour' metastases to a parathyroid adenoma (Chrisoulidou et al 2012, Lee et al 2013, Shifrin et al 2015, Bauer et al 2018. Thymic neuroendocrine tumour metastatic to the parathyroids has been reported in a case of a patient with multiple endocrine neoplasia (MEN1) syndrome and an enlarged parathyroid gland (Shifrin et al 2015).…”
Section: Epidemiologymentioning
confidence: 99%
“…Owing to their anatomic location, adjacent to the thyroid, parathyroid glands should be at high risk of tumor involvement in patients with TC. Unexpectedly, only four thyroidectomy-based series of adult patients have been as yet reported in the literature [ 4 7 ], describing parathyroid invasion by TC, of which three originated from the same institution, the Kuma Hospital in Japan [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%